(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Preeclampsia is a multifactorial pregnancy-specific disorder which is symbolized by the development of hypertension and proteinuria after 20 weeks of gestation. With the greatest morbidity and mortality, preeclampsia affects 5% to 7% of all pregnant women. Material And Method: 390 subjects were included in the study and were grouped. Results: Mean maternal age of cases in years was observed as 26.68±4.2, mean gestational age in weeks was 36.2. Systolic and diastolic BP in mmHg was 159.4 and 104.8 respectively. Mean weight was observed as 72.6 Kg and Height was 158.4 cm. There was statically significant correlation observed between vitamins in Group I and Group II, but Vitamin E and Vit B 12 does not show any significant correlation between them. No Stastical significance were found in the vitamins level in Group III and Group II. Statistically significant difference was observed between group I and Group III, for vitamin B12, vitamin D, vitamin C and vitamin A. No statistical significance difference was observed in vitamin E levels. Conclusion: The intended intervention of Vitamins has a protective effect against recurrent preeclampsia. Vitamins supplementation therapy in pregnancy could help in reducing the incidence of gestational hypertension/preeclampsia.